UPAYA UNIT KAMSEL POLRESTA SURAKARTA GUNA MENCEGAH KECELAKAAN LALU LINTAS DI POLRESTA SURAKARTA - RAFY PUTRA HIBATULLAH (Police Studies Review, 2022)
The background of writing this final project is the high number of accidents that occur on Jl. Surakarta veteran for the last five years. The purpose of writing this final project aims to describe the problems that cause problems and find solutions with the hope that the number of accidents on Jl. Surakarta veterans are declining. The author uses SWOT Analysis Theory and Management Theory then the author also uses the concept of Social Education and the concept of effort. With the research area at Polresta Surakarta, writing this final project uses a qualitative approach and data collection techniques of observation, interviews, and document studies. The results of this study found several problems in the implementation of traffic accident prevention on Jl. Veterans of Surakarta and also problems with the efforts of the South and West Security Unit to prevent traffic accidents on Jl. Surakarta Veterans. The conclusion that the author got during the research is not a concern that Jl. Veteran Surakarta is accident prone but Jl. Surakarta Veterans have been classified as accident-prone points by the Surakarta Police Traffic Unit.